Determining the potential Benefits of Using Primavera P6 Technology in Sustainability and Construction Project in Libya - Almayouf, Khaled Omar; Shahran, Abdrahman Faraj (Sharwes Scientific Journal, 2022)
The sustainability of construction projects in Libya is influenced by factors like the lack of enough building resources, poor planning, implementation approaches, and high construction costs. As every engineering sector advances each data, construction industries and not exempted. With Primavera P6 Technology, the construction of companies has been able to organize, plan, schedule, and manage the resources in a better way. Increased construction activities in Libya have made it difficult to make a proper plan and accomplish the project promptly. The data collectively, through a combination of interview and survey, reveals that Primavera P6 Technology serves as essential tool that aid in handling the issue of resources, planning, raw materials, and sustainability issues affecting the organization.